Molecular identification of Candida spp. isolated from women with vulvovaginal candidiasis in Koya District, Iraq 1 - Mohammed, Kale Mohammed Ali; Zrary, Taha Jalal Omar (Sulaimani Journal for Pure and Applied Sciences, 2023)
Vulvovaginal candidiasis (VVC) is the second most common vaginal infection among women of reproductive age. It is an opportunistic mucosal infection. Candida species causes VVC, which affects millions of women annually. The objective of this study was to isolate and identify the species of Candida from married women who had VVC attending Shahid Doctor Khalid Hospital & Haji Qader Health Centre in Koya, Iraq using traditional and molecular methods. This research was carried out, from December 2021 to May 2022; 150 vaginal swabs from married patients with symptoms of VVC were collected. Swabs were microscopically examined, grown on Sabouraud Dextrose Agar (SDA), and HiCrome™ Candida Differential agar and Germ Tube Test were used to identify Candida isolates. Next, the results were validated using the molecular method called polymerase chain reaction (PCR) to amplify and detect the ITS region in this study. The chitin synthase gene (CHS1) confirmed all C. albicans isolates. Out of the 150 vaginal swabs gathered, 84 (56%) cases were positive for vaginal candidiasis. Ages 26-30 were found to have the most significant proportion of positive patients, and Women who were pregnant had a more positive culture than women who were not. Identifying six different species of Candida was accomplished through the application of both traditional and molecular techniques in the study; they are C. albicans (88.1%), C. glabrata (4.8%), C. kefyr (2.4%), C. krusei (2.4%), C. parapsilosis (1.2%), and C. tropicalis (1.2%). Finally, we concluded that VVC was shown to be prevalent in Koya city, with the predominant species as C. albicans among all other species.
Keywords: Vulvovaginal candidiasis; Prevalence; PCR; Candida species; Candida albicans